2020
DOI: 10.1016/j.ijid.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of coronavirus disease 2019 in Daegu, South Korea

Abstract: Highlights Among 694 inpatients with COVID-19, 137 patients were classified as severe. No severe case was observed among patients aged ≤ 19 years. Asymptomatic patients accounted for 14.4% of cases. The first outbreak was primarily associated with younger age groups. The number of severe patients and the mortality rate were high in the second outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 15 publications
3
50
0
2
Order By: Relevance
“…A total of 5,332 records were excluded after screening the titles/abstracts because they did not match our inclusion and exclusion criteria. After evaluating 38 full-texts for eligibility, 6 full-text articles were excluded because they do not have the control/comparison group, 5 full-text articles were excluded because they do not have the outcome of interest (risk of COVID-19 infection, severe COVID-19, and mortality), 3 full-text articles were excluded because the articles were not in English, and finally, 24 studies ( Atkins et al, 2020 , Bianchetti et al, 2020 , Covino et al, 2020 , Docherty et al, 2020 , Giorgi Rossi et al, 2020 , Harrison et al, 2020 , Hong et al, 2020 , Hwang et al, 2020 , Jang et al, 2020 , Ji et al, 2020 , Kabarriti et al, 2020 , Knights et al, 2020 , Kokoszka-Bargieł et al, 2020 , Lee et al, 2020 , Miyashita et al, 2020 , Mohamed et al, 2020t , Moon et al, 2020 , Nystad et al, 2020 , Poblador-Plou et al, 2020 , Rozenfeld et al, 2020 , Sapey et al, 2020 , Sung et al, 2020 , Wan et al, 2020 , Yang et al, 2020 ) with a total of 4,648,247 sample size and 46,391 dementia patients were included in the meta-analysis ( Figure 1 ). Of a total of 24 included studies, 21 were retrospective cohort, 2 studies were prospective cohort, while the remaining 1 study was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5,332 records were excluded after screening the titles/abstracts because they did not match our inclusion and exclusion criteria. After evaluating 38 full-texts for eligibility, 6 full-text articles were excluded because they do not have the control/comparison group, 5 full-text articles were excluded because they do not have the outcome of interest (risk of COVID-19 infection, severe COVID-19, and mortality), 3 full-text articles were excluded because the articles were not in English, and finally, 24 studies ( Atkins et al, 2020 , Bianchetti et al, 2020 , Covino et al, 2020 , Docherty et al, 2020 , Giorgi Rossi et al, 2020 , Harrison et al, 2020 , Hong et al, 2020 , Hwang et al, 2020 , Jang et al, 2020 , Ji et al, 2020 , Kabarriti et al, 2020 , Knights et al, 2020 , Kokoszka-Bargieł et al, 2020 , Lee et al, 2020 , Miyashita et al, 2020 , Mohamed et al, 2020t , Moon et al, 2020 , Nystad et al, 2020 , Poblador-Plou et al, 2020 , Rozenfeld et al, 2020 , Sapey et al, 2020 , Sung et al, 2020 , Wan et al, 2020 , Yang et al, 2020 ) with a total of 4,648,247 sample size and 46,391 dementia patients were included in the meta-analysis ( Figure 1 ). Of a total of 24 included studies, 21 were retrospective cohort, 2 studies were prospective cohort, while the remaining 1 study was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13,51-96 , Egypt 97 , France 98-101 , Germany 102 , India 103,104 , Italy [105][106][107][108][109][110][111] , Japan 112,113 , Jordan 114 , Somalia 115 , South Korea 116,117 , Spain 118,119 , Turkey 120,121 , and the US [122][123][124][125][126] . Two studies were cross-sectional 119,122 , five were prospective cohort studies 65,90,98,110,121 and the remaining 71 studies were retrospective studies.…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…Another study which involved 46 patients reported that 40 (86%) had tension-type pain and 6 (14%) had migraine-like headache 107 . Data from 18 studies indicated that 72.17% (236/327) of headaches were reported in mild-moderate COVID-19 cases 51,53,55-58,62,63,67,76,88,92-97, 117 . The prevalence of headache in severe COVID-19 cases from 15 studies was 27.83% (86/309) 53,55,57,58,62,63,73,76,88,92,93,95-97,117 .…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…A study with COVID-19 with Daegu population was published and reported that mortality as 2.6% (18/694) and significant risk factors for severe disease were lymphopenia, lactate dehydrogenase, C-reactive protein, and low albumin in the study. 28 However, the study was conducted with univariate analysis. 28 A study with COVID-19 with 352 Korean patients (hospitalized in Dongguk University Gyeongju Hospital and the Andong Medical Center) with multi-variable regression analysis reported age (≥ 70 years), a history of malignancy, fever (≥ 37.5°C), and diabetes were significant risk factors of mortality.…”
Section: Discussionmentioning
confidence: 99%